Medication administration: acquisition of knowledge and abilities required for a group of nurses (Revista Latino-Americana de Enfermagem, 2004)
Nowadays, it is known that medication administration is a multidisciplinary process and requires constant updating from the professionals in charge. However, lack of knowledge, updating and in-service education permeate this theme area. Goals: analyze the educational needs of nurses working at a university hospital in the interior of São Paulo State, Brazil with regard to medication administration, as well as discuss about the need for this group of nurses to obtain the required knowledge and abilities. The Nominal Group Technique was used by means of the following question: "What else do you need to know in order to complete your knowledge on medication administration?" Eight categories of educational needs emerged: medication effect mechanisms, medication preparation and administration, information and knowledge acquisition, medication interactions, medication stability, specific and chemotherapeutic medication, side effects of medication and other aspects of medication administration. An updating course was proposed on the basis of the identified educational needs.